Rheological Properties of a Sodium Bentonite and Lactose Aqueous Dispersion - Morals, L. C. [UNESP]; Rosa, André Henrique [UNESP]; Fraceto, L. F. [UNESP]; Toledo, A. C. T.; Campos, V. [UNESP] (Trans Tech Publications Ltd, 2012)
Aim of this paper is show the viscosity measure of a sodium bentonite-water-lactose mixture and your rheological behaviour. This analysis showed the formation of tridimensional structure type and formation of stratified silicate/lactose, this occurred due to different concentrations of organic products into mixture and due to a difference of rotation during viscosity measument. Formation of networks is a consequence of the attraction between the silicate layers in water-lactose mixture. In the present work aqueous solutions of lactose with concentration of 7%, 5%, 3%, 1% and 0% (wt %) were used.
Keywords: Sodium bentonite-water-lactose; viscosity and rheological